Floer homology groups in Yang-Mills theory - Donaldson, S. K. (Cambridge tracts in mathematics, 2001)
The seminal work of Floer has now been placed in a contemporary setting. The author of this monograph writes with the big picture constantly in mind, reviewing current knowledge and predicting future directions. This forms part of the work for which Simon Donaldson was awarded the prestigious Fields Medal.